QARAQALPAQSTANDA MÁDENIY-AǴARTÍWSHÍLÍQ JUMÍSLARÍNÍŃ RAWAJLANÍWÍNDA MILLIY ZÍYALÍLAR XÍZMETI (1920-30-j) - Saǵındikov, B. (SCIENCE and SOCIETY, 2021)
The article studies the issues of the formation of the Karakalpak cultural and educational work in the 20-30 s of XX century. It was analyzed the cultural and educational work of the Karakalpak national figures in the field of education, culture and art during the period of the totalitarian regime.